Desigualdades raciais e de gênero na mortalidade geral no ELSA-Brasil: uma abordagem interseccional - Fernanda Esthefane Garrides Oliveira (2018)
One of the main faces of racial inequalities in health in Brazil is revealed by the lower life expectancy of blacks and browns (pardos) in relation to whites, that adds up to the gender inequalities in the risk of dying. The intersectionality theory points out that multiple social identities, such as race/skin color and gender, interact and define distinct experiences in the social structure, producing and maintaining inequities in health. This dissertation investigated whether self-reported race/skin color, gender and intersection of race/skin color-gender were associated with the risk of dying in a mean follow-up period of 7 years among adults in the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). ELSA-Brasil is a multicenter cohort that included 15,105 servers of public educational institutions and research from six Brazilian cities. In this analysis were excluded participants without information of race/skin color (184), who indicated yellow (Asians) race/skin color (374) or indigenous (157) and those who died before the end of the first year of follow-up (25). The time at risk for those eligible in the study corresponded to the period between one year after entry into the cohort and death or right censoring. Were included deaths from all causes occurred one year after entering the cohort until July 2018. The explanatory variables of interest were self-reported race/skin color, gender and intersection of race/skin color-gender (white women, brown women, black women, white men, brown men and black men). Potential confounders included were measured at the study baseline. Cox proportional hazards models were used to estimate the Hazard Ratio (HR) and intervals with 95% confidence (CI 95%) of the strength of association between the variables of interest and time to death. Participants totaled 100,407.2 person-years and 441 deaths (3.1%) were recorded. After all adjustments, compared to those of race/skin color white, the black group (HR:1.31; IC95%:1.001-1.72) and brown group (HR:1.27; IC95%:1.002-1.61) were at higher risk of dying; men were also at higher risk than women (HR:1.62; IC95%:1.32-2.00). In relation to race/skin color-gender groups, there were no significant differences in the risk of dying of black and brown women when compared to the white women group, while it was observed an increase in the risk of dying from 52% among white men (HR: 1.52; IC95%:1.13-2.06), 96% among brown men (HR:1.96; IC95%:1.40-2.74) and 118% among black men (HR:2.18; IC95%:1.50-3.19). The results confirm racial inequalities in the risk of dying and reveal that the differences may be even greater when taking into account social subgroups established at the intersectionality of race/skin color and gender. Considering the intersectionality of social identities is essential to reveal the aspects that drive health inequalities and to contribute to guiding effective public policies in promoting equity.